2002
DOI: 10.1039/b200123n
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term exposure to mosquito coils: residual deposition and dissipation of d-trans-allethrin in a room

Abstract: A D-trans-allethrin-based mosquito repellent coil formulation was used continuously in a room for 30 d. Two different experiments were conducted and the deposition of residues on different surfaces of the room was determined. Studies were conducted continuously for a period of 30 d in a fully closed room and in another room kept open for 14 h per day. The residues deposited on different surfaces, ceiling, side walls and floor, were measured. The results showed the accumulation of high concentrations of allethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…EU commission directive 96/46 section 4.2.5 requires analytical methods for the determination of residues in body fluids and tissues for pesticides classified as toxic or very toxic. In view of the greater demand for the sensitive analytical techniques related to monitoring the human health and environment [23][24][25][26][27][28][29][30][31] and in continuation of our investigations on occupational exposure [32][33][34], the present studies are aimed at developing a rapid and high sensitive method for the sequential determination of residues of different pyrethroid molecules in whole blood. The applications of the method was investigated in human population exposed to pyrethroid based formulations.…”
Section: Introductionmentioning
confidence: 99%
“…EU commission directive 96/46 section 4.2.5 requires analytical methods for the determination of residues in body fluids and tissues for pesticides classified as toxic or very toxic. In view of the greater demand for the sensitive analytical techniques related to monitoring the human health and environment [23][24][25][26][27][28][29][30][31] and in continuation of our investigations on occupational exposure [32][33][34], the present studies are aimed at developing a rapid and high sensitive method for the sequential determination of residues of different pyrethroid molecules in whole blood. The applications of the method was investigated in human population exposed to pyrethroid based formulations.…”
Section: Introductionmentioning
confidence: 99%
“…From earlier studies, a substantial amount of allethrin residues are accumulated on different surfaces and are persistent (World Health Organization 1989, Ramesh & Vijayalakshmi 2002. Even though pyrethroid-based mosquito repellents have been used for several years, reports on their microbial degradation are few.…”
Section: Discussionmentioning
confidence: 99%
“…Several hundred tonnes per year of allethrin, prallethrin, bioallethrin, esbiothrin and other pyrethroid are manufactured and used throughout the world (Ramesh & Vijayalakshmi 2002). Allethrin disrupts Na + channels (Bloomquist 1996) and can also act as dermal and respiratory allergen (Yamamoto 1970).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concentration of transfluthrin in the gas phase decreased to the level before MR application within 16 h after removing the electric vaporizers (Vesin et al, 2013). Ramesh and Vijayalakshmi (2002) analyzed residual concentrations of allethrin emitted from mosquito coils on indoor surfaces, and found that allethrin residues in surface dust in a room with the window open were about 10 times lower than that in a closed room. They also found that residual allethrin on the surfaces in the window-open room was completely dissipated within 15 d after the mosquito coil was removed, but residues of allethrin in the closed room still accounted for one third of the concentrations at the point of extinguishment.…”
Section: Dissipation Of Pyrethroids From the Mr Applicationmentioning
confidence: 99%
“…This distribution then influenced the route and extent of potential human exposure to these contaminants (Ramesh and Vijayalakshmi, 2002;Sanusi et al, 1999). In general, particle-associated pyrethroids are more easily deposited on various surfaces, while gaseous compounds have a greater tendency to remain in the air (Matoba et al, 2004;Vesin et al, 2013).…”
Section: Gas-particle Partitioning Of Pyrethroids During the Mr Applimentioning
confidence: 99%